Monotherapy for hepatitis B infection: a review of treatment options. Issue 12 (2nd December 2015) - Ozaras, Resat; Khodor, Hawa'a; Yetim, Nergul; Unal, Umut Kaan; Demirhan, Yunus Emre; Gultekin, Goknil; Isal, Burak
Abstract : Chronic hepatitis B (CHB) is a global health problem, causing liver failure, cirrhosis and hepatocellular carcinoma. CHB treatment aims to prevent liver-related complication. The treatment of CHB infection includes monotherapy with either interferons (IFNs) or nucleos(t)ide (NUC) analogs. IFNs have moderate antiviral effects, and their use is limited by side effects. With the availability of NUCs, IFN-intolerant and decompensated cirrhotic patients began to be treated. Lamivudine and telbivudine, nucleoside analogs, have low genetic barrier to resistance. Adefovir, a nucleotide analog, has moderate potency and potential nephrotoxicity. Entecavir and tenofovir, with their high potency, high genetic barrier to resistance and favorable safety profile are the standard of care in CHB treatment. Long-term use of NUCs with maintained viral suppression results in a decrease in liver-related complications.